Student Stratification among a Combination of School Choice Policies in Detroit. Issue 1 (2nd January 2020) - Singer, Jeremy
ABSTRACT: A large body of research on school choice has examined whether choice-based policies reproduce and exacerbate existing racial and socioeconomic inequalities. While many states have enacted multiple school choice policies at once, most of these studies focus on a single choice-based policy. This study examines enrollment patterns in Detroit in the context of a combination of school choice policies: charter schools, intra-district choice, and inter-district open enrollment. It assesses the extent to which Detroit students are stratified by race, socioeconomic status, and special education status, and describes how different socio-spatial push and pull factors may be associated with different options for school choice. Even among Detroit's racially and socioeconomically homogeneous student population, the results show some evidence of a stratified educational landscape, and suggest the need for more research on how a combination of choice mechanisms may be taken up differently by different students and families.